An inquiry into the nature of the gamma-ray source 3EG J1828+0142 - Punsly, Brian (2000)
The unidentified, low-latitude, gamma -ray source 3EG J1828+0142 presents high levels of variability and a steep spectral index Gamma ~ 2.7. Here we propose a model for this source where the high-energy emission is produced by a galactic Kerr-Newman black hole. The model takes into account electron-positron annihilation losses in the calculation of the expected spectral energy distribution and can reproduce the observational features, including the absence of a strong radio counterpart. We also report the discovery of a nearby supernova remnant that could be associated with the original supernova explosion that created the black hole. Several faint radio sources were also detected in the radio field within the inner gamma -ray confidence contour and their spectral index estimated. Some of these sources could be the expected weak radio counterpart.